2010
DOI: 10.1177/0269215509353263
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of motor impairments to limitations in activity and restrictions in participation in adults with hemiplegic cerebral palsy

Abstract: The findings imply that coordination of four motor impairments makes the largest independent relative contribution to activity limitations, whereas upper limb activity makes less contribution to participation in people with mild and moderate hemiplegic cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Whereas the current study was the first to quantify the effect of an eligible impairment on a paralympic sport, one other study investigated the strength of association between a standardized upper limb activity assessment and four measures of impairment: ROM, coordination, strength, and spasticity (2). Results indicated that 25% of the variance in the upper limb assessment was explained by a combination of ROM, coordination, spasticity, and strength (2), indicating that there may have been an interaction between the measures of impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the current study was the first to quantify the effect of an eligible impairment on a paralympic sport, one other study investigated the strength of association between a standardized upper limb activity assessment and four measures of impairment: ROM, coordination, strength, and spasticity (2). Results indicated that 25% of the variance in the upper limb assessment was explained by a combination of ROM, coordination, spasticity, and strength (2), indicating that there may have been an interaction between the measures of impairment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this phenomenon is also found in other diagnosis groups. 27,28 Even when all body functions that enhance manual activity capacity score 0 preoperatively and maximum postoperatively, the maximum increase in manual activity capacity for the dominant hand may be 11 points. On the other hand, for the nondominant hand this all may add up to 33 points on a scale from 0 to 36.…”
Section: Discussionmentioning
confidence: 99%
“…While the current study was the first to quantify the effect of an eligible impairment on a Paralympic sport, one other study investigated the strength of association between a standardised upper limb activity assessment and four measures of impairment -ROM, coordination, strength and spasticity (Chiu et al 2010). Results indicated that 25% of the variance in the upper limb assessment was explained by a combination of ROM, coordination, spasticity and strength (Chiu et al 2010), indicating that there may have been an interaction between the measures of impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that 25% of the variance in the upper limb assessment was explained by a combination of ROM, coordination, spasticity and strength (Chiu et al 2010), indicating that there may have been an interaction between the measures of impairment. Two results from the current study were consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation